First molecular report of causative agent of otomycosis due to Aspergillus luchuensis. (2nd September 2021) - Sarvestani, Hasti Kamali; Ghazvini, Roshanak Daie; Hashemi, Seyed Jamal; Rezaie, Sassan; Mahmoudi, Shahram; Shoar, Mohsen Gerami; Elahi, Miad; Izadi, Alireza; Getso, Muhammad Ibrahim; Rafat, Zahra; Tajdini, Ardavan; Hedayati, Mohammad Taghi
Abstract : Otomycosis is a fungal infection of the external auditory canal caused mainly by the genus Aspergillus. Aspergillus luchuensis, an industrially important fungus, is a member of Aspergillus section Nigri . In this report, we present a case of otomycosis due to Aspergillus luchuensis in a 43-year-old female patient. We performed a partial PCR-sequencing of β-tubulin and calmodulin genes to identify the isolate to the species level. Further, we determined the in vitro susceptibility of the isolate to nystatin, clotrimazole and itraconazole according to the Clinical & Laboratory Standards Institute (CLSI) M38-A2 protocol. Accordingly, the minimum inhibitory concentrations of clotrimazole, nystatin and itraconazole were 0.25μg/mL, 0.5μg/mL and 1μg/mL, respectively. This is the first report of clinically relevant isolation of Aspergillus luchuensis identified by a molecular technique as a causative agent of otomycosis.